Descriptive study of knowledge, attitudes and individual behavior of East Java MSMEs related to halal culture - Siti Asmaniyah Mardiyani; Mas'ud Said; Nour Athiroh; Eko Noerhayati (Universitas Airlangga, 2022)
This study aims to measure aspects of the knowledge and attitudes of MSMEs in the food and beverage sector towards halal culture in their businesses. This is important to see the readiness of MSMEs to face the era of the halal industry. The research approach used is descriptive quantitative. Data collection was carried out using an online questionnaire for 83 MSME respondents in East Java, including Malang Raya, Pasuruan, Blitar, Lumajang, and Kediri. The results showed that most of the respondents (92.41 percent) had a high level of knowledge and the rest had a moderate level of knowledge. This condition shows that the level of knowledge of MSME actors regarding halal culture is very good. The results of the analysis further provide information that 87.50 percent of MSME actors have good halal cultural behavior, 10.42 percent have a moderate level of behavior, and only 2.08 percent have low behavioral attitudes. This research illustrates that MSME actors in East Java have the potential and readiness to support the development of the halal industry